Professional of the highest test. (Herald of Journalism, 2016)
The article is devoted to the 75 anniversary since the birth of the first Minister of Education of the Republic of Kazakhstan Shaysultan Shayakhmetov heading profile department during the most difficult period in the history ofthe republic – from 1987 to 1993. Disorder of the USSR and difficult years of formation of the young independent state caused a raising of a wave of migration, outflow from schools of skilled teachers, poverty of material baseof educational institutions. Despite it Sh. Shayakhmetov not only kept, but also started reforming an education system of the new sovereign state.
Keywords: Republic of Kazakhstan; education; minister; ministry; law; sovereignty; reform; school; educational institution